"I will give you a mouth and wisdom": Prudent speech in Luke 21:15. (November 2015) - Shiell, William D.
Luke 21:15 is normally translated to the effect that Jesus will give his disciples "words and wisdom." The ancient audience, however, when hearing this text from a lector, likely would have understood this phrase to be directed to them and to mean that Jesus would provide them with "a mouth and wisdom." In the ancient world, the mouth functioned to organize one's thoughts, provide a window on the character of the one speaking, and to provide a potential source of wisdom. When on trial, defendants needed to know what to say, and when to speak. Thus, this text, as heard by the ancient audience, would have served as Jesus' promise of enabling them to speak prudently when standing trial for their faith.